A note on stochastic volatility, GARCH models, and hyperbolic distributions - Stefan R. Jaschke (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
We establish a relation between stochastic volatility models and the class of generalized hyperbolic distributions. These distributions have been found to fit exceptionally well to the empirical distribution of stock returns. We review the background of hyperbolic distributions and prove stationary distributions of certain GARCH-type models to be generalized hyperbolic.
urn:nbn:de:kobv:11-10056700
Keywords: 330